2008
DOI: 10.1176/ps.2008.59.7.732
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Staff Turnover in the Implementation of Evidence-Based Practices in Mental Health Care

Abstract: The behavioral health workforce remains in flux. High turnover most often had a negative impact on implementation, although some teams were able to use strategies to improve implementation through turnover. Implementation models must consider turbulent behavioral health workforce conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(64 citation statements)
references
References 30 publications
3
53
0
8
Order By: Relevance
“…However, these interventions are rarely routine in settings where most people receive services (1). Lack of community-based implementation of evidence-based treatments may be due in part to challenges faced by those seeking to implement treatments, such as selecting staff to train, buffering implementation efforts to withstand the negative impact of high staff turnover (2), maintaining treatment model fidelity, and maintaining administrative support (3). …”
mentioning
confidence: 99%
“…However, these interventions are rarely routine in settings where most people receive services (1). Lack of community-based implementation of evidence-based treatments may be due in part to challenges faced by those seeking to implement treatments, such as selecting staff to train, buffering implementation efforts to withstand the negative impact of high staff turnover (2), maintaining treatment model fidelity, and maintaining administrative support (3). …”
mentioning
confidence: 99%
“…Additionally, many therapists could not be reached by email due to transitioning out of their jobs after initial training. This is not surprising, as a recent study found voluntary turnover rates as high as 80% in an evidence-based implementation effort [29]. It is possible that the four scales utilized in this study are not independent, but rather tapping into larger constructs of overall dissemination effectiveness in therapist practice.…”
Section: Discussionmentioning
confidence: 61%
“…A maioria dos serviços é prestada fora dos locais usuais de atendimento à saúde mental, incentivando a integração na comunidade. Desde os anos 1980, o modelo ACT foi replicado em vários locais, como Estados Unidos, Europa e Canadá, e estudos têm demonstrado bons resultados relacionados à diminuição de taxas de hospitalização, melhor qualidade de vida e altos níveis de satisfação do cliente e da família 8,10,31,40 . Também por ser uma das intervenções mais conduzidas, possui mais de um método de medida da fidelidade, incluindo mais de uma escala de avaliação (DACTS, TMACT, Ontario ACT Program Fidelity Too) e variações do meio de obtenção dos dados (aplicação das escalas por telefone) 9,35,36,38,40 .…”
Section: Discussionunclassified
“…Pessoas com distúrbios duais têm pior prognóstico do que aqueles com um só transtorno. Comparado às demais intervenções, o tratamento integrado de transtornos duais foi uma das práticas que mais foram executadas com baixa fidelidade 31,34 . Talvez isso se associe ao fato de que essa intervenção não tem se mostrado consistentemente superior em comparação com os tratamentos usuais para essa população em todos os estudos, necessitando de mais pesquisas a respeito.…”
Section: Discussionunclassified